ANALISIS KEBUTUHAN TENAGA KERJA PERIKANAN TINGKAT MENENGAH UNTUK MEMENUHI INDUSTRI PERIKANAN TANGKAP DI INDONESIA - Sugeng Hari Wisudo; Lilly Aprilya Pregiwati; Iin Solihin (Buletin PSP, 2007)
Condition of fisheries manpower makes important role on supporting policies for the Ministry of Marine Affairs and Fisheries. Especially in fishery sector, the manpower competency is proved by issuing deck and engine certification of competency. The certificate is one of the fishing vessel personnel standard certificate which implemented the international mandate of IMO, FAO and ILO. The recent problem is how far demand of the manpower meets the supply, due to rapid development of vocational high school chiefly on producing middle level of fisheries manpower. The hypothesis is that demand and supply of middle fisheries manpower be inline and appropriate. The study is conducted to indicate middle fisheries manpower and fishing vessel at existing condition, to predict the need of manpower and to recommend strategic formulation for the manpower development. Existing condition of manpower and fishing vessel are conducted on the frame of survey. Projection of the manpower need was done by regression approach, and the recommendation for the manpower development is based on management strategic stages. Result of study covered time series of supply of manpower and fishing vessel quantity. Demand projection for manpower seemed unbalance of the supply and recommendation has been proposed. The study pointed out that the fisheries manpower supply just meet a demand about 10% of the necessity of sertified fisheries manpower. Projection of fisheries manpower for 2010 as 39,270 peoples. Main recommendation from the study is appropriate infrastructure and facilities as standardize to be provided.